PEMBELAJARAN PENDIDIKAN AGAMA ISLAM YANG MENYENANGKAN DENGAN MENDONGENG - Yekti Nugroho (Islamic University of Indonesia, 2018)
One of the learning strategies for early childhood education is storytelling, storytelling or storytelling, we can also use in teaching Islamic Education learning material. The learning challenge of Islan Religious Education at the level of early childhood is boredom and boredom caused by the stigmatization of teaching the same teacher. Storytelling not only conveys interesting and fun stories for children, but we can also insert moral values and even tell the history of the Prophet, student moral learning, train social sensitivity, perfect memorization of short letters, and the history of Islamic civilization. But of course there is a need for teachers to prepare interesting stories or stories, determine the media to be used such as teaching aids, master character, memorize storylines, present fairy tales with interesting techniques, prepare a comfortable place and prepare and practice before performing at front of children. So that the fairy tales delivered are not only able to meet the needs of children’s imagination and fantasy but also can shape the child’s personality, character and morals. Keywords: Learning, Education, Islam, Storytelling